Threat of mass resignation as a window of opportunity for questioning hospital service production structures in Finland - Kokkinen L; Viitanen E (Dove Medical Press, 2011)
Lauri Kokkinen1,2, Elina Viitanen11School of Health Sciences, University of Tampere, Tampere, 2Unit of Expertise for Work Organizations, Finnish Institute of Occupational Health, Turku, FinlandBackground: Service production structures of public health care, once established, have proved extremely difficult to change. For this study, we reviewed discussions that took place in management teams at a Finnish central hospital over a period of nine months. The aim of the research was to analyze whether the management team meetings brought forth new and radical alternatives as to how service production could be reorganized. In addition to this, we were also interested in any possible problems that could be solved using these alternative models of service production, and also how preconditions to the application of different alternatives came about and how they eventually concluded.Methods: Our data were derived from 24 management team meetings that took place between August 2007 and May 2008, and were fully videotaped. Data were collected from eight different management teams; the meetings of each were videotaped three times. The management teams reviewed represented three different hierarchical levels, ie, top management, division management, and operational unit management. Data were analyzed according to theory-based content analysis. As a theoretical framework, we utilized Kingdon’s model to enable us to understand why some issues and problems are brought to the agenda of the change process and go on to become concrete policies while others fail to do so.Results: During the study period, a threat of mass resignation of nursing staff caused a considerable change to the agenda of the management team meetings, introducing alternatives with the potential to renew the existing structures of operation in a radical manner.Conclusion: According to our analysis, the threat of mass resignation acted as a window of opportunity, linking the lack of nursing staff (problem) to operational and structural changes (alternative solutions).Keywords: hospital, nursing staff, mass resignation, change